Online Purchase in social media: An investigation on the factors encouraging consumers in Chennai - S., Athilinga Senjith; Chitra, K. (Ushus Journal of Business Management, 2026)
This study focuses on the factors encouraging the consumers to go for online purchase using social media. The study is descriptive in nature. The population of the study is general consumers buying products online through social media is unknown. The convenience sampling method was adopted to draw samples from the total population. The sample size is 138 consumers from Chennai city. 48.5 % of the consumers were Entrepreneurs and 48.5% of the consumers are using Instagram for online purchase. 59.4% of the consumers are purchasing products online when needed. Cash on delivery ranked first and Door delivery ranked second for encouraging consumers to purchase products online. It is suggested to reduce impulse purchase while using social media. It is concluded that consumers should be aware about the process of purchasing products online and manage online and offline purchases equally to protect the welfare of the offline traders.